SirA Orthologs Affect both Motility and Virulence - Goodier, Robert I. (American Society for Microbiology, 2001)
The sirA gene of Salmonella enterica serovar Typhimurium encodes a two-component response regulator of the FixJ family that has a positive regulatory influence on the expression of type III secretion genes involved with epithelial cell invasion and the elicitation of bovine gastroenteritis. SirA orthologs in Pseudomonas, Vibrio, and Erwinia control the expression of distinct virulence genes in these genera, but an evolutionarily conserved target of SirA regulation has never been identified. In this study we tested the hypothesis that sirA may be an ancient member of the flagellar regulon. We examined the effect of a sirA mutation on transcriptional fusions to flagellar promoters (flhD, fliE, fliF, flgA, flgB, fliC, fliD, motA, and fliA) while using fusions to the virulence gene sopB as a positive control. SirA had only small regulatory effects on all fusions in liquid medium (less than fivefold). However, in various types of motility agar plates, sirA was able to activate a sopB fusion by up to 63-fold while repressing flagellar fusions by values exceeding 100-fold. Mutations in the sirA orthologs of Escherichia coli, Vibrio cholerae, Pseudomonas fluorescens, and Pseudomonas aeruginosa result in defects in either motility or motility gene regulation, suggesting that control of flagellar regulons may be an evolutionarily conserved function of sirA orthologs. The implications for our understanding of virulence gene regulation in the gamma Proteobacteria are discussed.